Vendetta. Theory and practice of conflicts resolution - Patrizia Resta (EtnoAntropologia, 2015)
Taking as ethnographic material the blood feud in Albania in the twentieth century, this article aims to show that both the blood feud and the feud are manifested through the exercise of violence and according to the defense of moral or material interests of a group. Nevertheless, they respond to a  different logic. The general assumption of this study is that the values of the feuding paradigm are negotiable; as such, they can be at play and can be constantly modified even in contexts functionally renewed.